The Biological Activities of Lavandula stoechas L. against Food Pathogens - Gülten Ökmen (International Journal of Secondary Metabolite, 2017)
Foodborne pathogens are microorganisms as well as a number of parasites, which are capable of infecting humans via contaminated food or water. In recent years, diseases caused by foodborne pathogens have become an important public health problem in the world, producing a significant rate of morbidity and mortality. In traditional medicine, numerous plants and their extracts have used for thousands of years to treat health disorders. Although many studies were made on natural herbs, those involving the antimicrobial, antioxidant and antimutagenic activity of the herb species are rather rare. This study researches the biological activities of ethanol and methanol extracts of Lavandula stoechas L., which are prevalent in Turkey. In this study, 8 food pathogens were used for antimicrobial activity studies. Antimicrobial activity studies were done by disk diffusion assay and MIC (minimum inhibitory concentration). DPPH method was used for non-enzymatic antioxidant activity. The Lavandula extracts were screened for their antimutagenic activity against sodium azide by Ames test in absence of rat microsomal liver enzyme (-S9). The ethanol and methanol extracts of Lavandula stoechas showed antibacterial activity (7 mm) against most of bacteria. The antifungal activity of L. stoechas was not determined against C. albicans RSKK02029. The lowest MIC value was determined as 3250 µg/mL. The highest radical inhibition was determined as 79 % by Lavandula stoechas flower methanol extract. The flower extract of L. stoechas (12500 µg/plate) was found to have its highest antimutagenic activity for Salmonella Typhimurium TA98. This inhibition value is 42 %. L. stoechas leaves extracts (6250 and 3125 µg/plate) showed a moderate positive inhibitory effect for Salmonella Typhimurium TA98, and TA100. L. stoechas flower extracts (12500 and 6250 µg/plate) showed a moderate positive inhibitory effect (respectively 31 and 30 %) for Salmonella Typhimurium TA100. The extracts of L. stoechas have antimicrobial, antioxidant and antimutagenic activities.